2019
DOI: 10.1136/bmjopen-2018-027946
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent preventive treatment of pregnant women in Kintampo area of Ghana with sulphadoxine-pyrimethamine (SP): trends spanning 2011 and 2015

Abstract: ObjectiveIn Ghana, intermittent preventive treatment during pregnancy with sulphadoxine-pyrimethamine (IPTp-SP) is recommended for the prevention of malaria-related adverse outcomes. This study demonstrates the coverage of IPTp-SP use among pregnant women over a period (2011–2015) and the impact of various sociodemographic groups on the uptake of IPTp-SP.DesignRetrospective analysis using data from all pregnant women in the Kintampo Health and Demographic Surveillance System area on the uptake of IPTp-SP.Setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 30 publications
9
28
1
Order By: Relevance
“…The uptake of three or more doses of SP was reported to be 8% countrywide which is still low than the recommended coverage of 80% from WHO and Roll Back Malaria (RBM) benchmark target (3). This was also observed in several studies conducted in other sub-Saharan countries (20)(21)(22)(23). Hence, the urgent need to plan effective strategies to improve IPTp-SP coverage and uptake in sub-Saharan Africa.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The uptake of three or more doses of SP was reported to be 8% countrywide which is still low than the recommended coverage of 80% from WHO and Roll Back Malaria (RBM) benchmark target (3). This was also observed in several studies conducted in other sub-Saharan countries (20)(21)(22)(23). Hence, the urgent need to plan effective strategies to improve IPTp-SP coverage and uptake in sub-Saharan Africa.…”
Section: Discussionsupporting
confidence: 84%
“…This is because educated pregnant women could be aware and knowledgeable on the importance and bene ts of using SP for malaria prevention during pregnancy. Similarly, the ndings from Nigeria (24), Malawi (21,25), Ghana (22), and Zimbabwe (23) showed that the knowledge on the SP and on the consequences of not taking IPTp-SP as a facilitator toward the uptake hence the association between education level and the likelihood of the uptake of three or more doses of SP for malaria prevention during pregnancy.…”
Section: Discussionmentioning
confidence: 95%
“…ITNs have been shown to reduce maternal malaria parasitemia by 38%, malaria-related anemia by 47%, low birth weight by 23%, miscarriages/stillbirths by 33% and placental parasitemia by 23% [18,19]. Notwithstanding the importance of the WHO recommendations, recent evidence in Ghana suggest that compliance to the use of ITN and IPTp-SP remains low [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, most of the husbands living in the rural community did not know the significance of IPTp which intern to poor support to the women. This finding asserts the importance of awareness creation in the community through media and IPTp campaigns (22). Most of the respondents in the community mentioned that the SP at the PHC units is allegedly sold to patients which the poor can't afford.…”
Section: Discussionmentioning
confidence: 85%